(untitled) (Web of Teachers: Inderscience Research, 2023)
In the article, the primary school education system and content are currently in the process of updating and updating. One of the tasks of education is the formation of ecological consciousness. It is not only love and respect for all living beings, but also a sense of personal responsibility for what is happening around.